2019
DOI: 10.12924/of2019.05010052
|View full text |Cite
|
Sign up to set email alerts
|

Trials Evaluating Solarization and Tarping for Improved Stale Seedbed Preparation in the Northeast USA

Abstract: Stale seedbeds are commonly used by organic vegetable farmers to reduce in-season weed density. The primary purpose of this study was to evaluate the efficacy of soil solarization (clear plastic) with subsequent flaming for stale seedbed preparation. A secondary objective was to compare the efficacy of solarization with tarping (black plastic). Solarization is an established weed management practice in warmer climates, but its efficacy in the humid continental Northeast USA was unknown. We hypothesized that so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Afterwards, the area is rototilled and planted with a winter grain or a green manure crop [143]. Birthisel and Gallandt [144] found that solarization in Maine (cloudy climate) did reduce E. repens shoot density, at least in the short term. Unfortunately, the authors did not verify the vitality of the rhizomes exposed to solarization.…”
Section: Soil Disinfestationmentioning
confidence: 99%
“…Afterwards, the area is rototilled and planted with a winter grain or a green manure crop [143]. Birthisel and Gallandt [144] found that solarization in Maine (cloudy climate) did reduce E. repens shoot density, at least in the short term. Unfortunately, the authors did not verify the vitality of the rhizomes exposed to solarization.…”
Section: Soil Disinfestationmentioning
confidence: 99%
“…We applied tarps immediately after a precipitation event, but the lack of precipitation in May likely led to a soil water deficit that a single precipitation event was unable to overcome. The efficacy of tarping for weed control relies on adequate soil moisture, which may induce fatal germination of weed seeds (Birthisel and Gallandt, 2019). In dry years, irrigation before tarping may be necessary to make this system most effective.…”
Section: Fieldmentioning
confidence: 99%
“…The effects of tarping on weed community composition and diversity indicate that tarping, like tillage, can act as a strong filter on weed community assembly (Birthisel and Gallandt, 2019). Variability in how different weed species respond to levels and quality of cover crop mulch (Pittman et al, 2020;Teasdale and Mohler, 2000) show that cover crop mulch itself has a filtering effect on weed community assembly.…”
Section: Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Solarisation is an intensive form of stale seedbed preparation that utilises clear plastic to trap solar energy, heating soils to temperatures hot enough to kill weed seeds or seedlings (Horowitz et al, 1983;Standifer et al, 1984). We recently demonstrated that solarisation can result in mortality of weed seeds and reduced weed density (Birthisel and Gallandt, 2019) in the Northeast United States, suggesting that its applicability in temperate regions may be greater than previously assumed (Walters and Pinkerton, 2012). Efficacy of this practice generally increases with both ambient air temperature and soil moisture (Mahrer and Shilo, 2012), though it is also strongly affected by light intensity, which is impacted by cloudiness.…”
Section: Seedbank Reductionmentioning
confidence: 99%